1997
DOI: 10.1111/j.1600-065x.1997.tb00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Allorecognition by murine natural killer cells: lysis of T‐lymphoblasts and rejection of bone‐marrow grafts

Abstract: Natural killer (NK) cells of inbred mice reject allogeneic bone-marrow cells, and NK cells of F1 hybrid mice can reject parental bone-marrow cells (hybrid resistance). In some cases these patterns of rejection can be mimicked in vitro by utilizing IL-2 cultured NK effector cells and allogeneic or parental T-lymphoblasts as target cells. Lysis of allogeneic and parental targets in vitro can be explained on the basis of the missing self hypothesis. Subsets of NK cells that bear non-overlapping MHC class I inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 52 publications
1
28
0
1
Order By: Relevance
“…Although normal, resting spleen cells were not rejected upon Ly49C/I blockade other cell types may be more sensitive. Allogeneic and MHC-deficient BM cells can be rejected by NK cells [33,34] and activated T cells may express ligands for activating NK receptors and be more sensitive to NK-mediated lysis [32]. In our system, however, inhibitory receptor blockade did not induce rejection of CFSE-labeled syngeneic BM cells or Con A-activated T cells (Fig.…”
Section: Robust Self-tolerance After Ly49c/i Receptor Blockade In Vivomentioning
confidence: 64%
“…Although normal, resting spleen cells were not rejected upon Ly49C/I blockade other cell types may be more sensitive. Allogeneic and MHC-deficient BM cells can be rejected by NK cells [33,34] and activated T cells may express ligands for activating NK receptors and be more sensitive to NK-mediated lysis [32]. In our system, however, inhibitory receptor blockade did not induce rejection of CFSE-labeled syngeneic BM cells or Con A-activated T cells (Fig.…”
Section: Robust Self-tolerance After Ly49c/i Receptor Blockade In Vivomentioning
confidence: 64%
“…This represents one of only a few instances in which the results of bone marrow graft rejection is not reflected by its in vitro correlate (35,36). It has been suggested that the rejection of bone marrow grafts does not depend on the cytotoxic function of NK cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, Ly49A binds to D d and D k (3)(4)(5) (3). Functional in vitro studies have suggested that Ly49I transmits an inhibitory signal from H2 b , but not from H2 d (9). However, until the mAb 8H7, which binds Ly49I but not Ly49C, was developed, one could not be sure of the function of this NK cell subset.…”
mentioning
confidence: 95%